ANALISIS FAKTOR PERSEPSI RISIKO, LITERASI KEUANGAN, DAN TINGKAT PENDAPATAN TERHADAP PENGAMBILAN KEPUTUSAN INVESTASI DI PASAR SAHAM (STUDI PADA INVESTOR INDIVIDU SEKTOR PERBANKAN DI KOTA JAKARTA DAN TANGERANG TAHUN 2024: PERSPEKTIF AKUNTANSI PRILAKU) - Grissia Pearlyn; Michelle Kristian (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
Finding out how risk perception, financial literacy, and income level play a role in investment decisions is the driving force for this research. The research population consisted of one hundred seventy-eight individual investors hailing from the cities of Jakarta and Tangerang and the number that did not meet the criteria was eliminated, leaving one hundred and thirty-three individual investors who had investments in banking stocks. Online questionnaires were distributed using the convenience and snowball sampling, and data was analyzed using SPSS 30.0. This study found that people's level of risk perception, financial knowledge, and income level, had positive and substantial effects on their investment decisions. Banking companies should set stock prices that entice investors to put money into banking stocks, according to this study. Individuals should learn more about their own risk tolerance, become more financially literate, and develop investment plans that take their level of income into account as much as possible.